A Gate Design at Nyabikoni Campus Kabale University. - Gumisiriza, Benson (Kabale University, 2023)
Kabale university faculty of engineering is an institution of higher learning education which prepares and enables its students to carry out projects in different groups. This is done purposely to give knowledge to students about what is done in practical. Therefore, in compliance with the above mentioned above, my project was based on the gate design at Faculty of Engineering, Kabale University.